2021
DOI: 10.3390/life11121432
|View full text |Cite
|
Sign up to set email alerts
|

Considering Predictive Factors in the Diagnosis of Clinically Significant Prostate Cancer in Patients with PI-RADS 3 Lesions

Abstract: The use of multi-parametric magnetic resonance imaging (mpMRI) in conjunction with the Prostate Imaging Reporting and Data System (PI-RADS) is standard practice in the diagnosis, surveillance, and staging of prostate cancer. The risk associated with lesions graded at a PI-RADS score of 3 is ambiguous. Further characterization of the risk associated with PI-RADS 3 lesions would be useful in guiding further work-up and intervention. This study aims to better characterize the utility of PI-RADS 3 and associated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…[ 32 ]. Zhang et al also reported that PSAD could improve the detection of PCa, as well as csPCa, for PI-RADSv2 score-3 lesions [ 33 ]. Rico et al reported that PSAD improves the specificity and PPV, contributing to the improved management of csPCa [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ]. Zhang et al also reported that PSAD could improve the detection of PCa, as well as csPCa, for PI-RADSv2 score-3 lesions [ 33 ]. Rico et al reported that PSAD improves the specificity and PPV, contributing to the improved management of csPCa [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many efforts have been made to identify new biomarkers that could improve PCa detection. PSA density (PSAD) is a clinically useful tool to compensate for the low sensitivity of PSA, and recent studies have reported that PSAD is effective in determining whether to perform a prostate biopsy and improves the detection of PCa and clinically significant PCa (csPCa) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%